Border Theory : The Limits of Cultural Politics - Michaelsen, Scott (Book collections on Project MUSE., 1997)
The authors gathered in this volume examine the multiple borders that define the United States and the Americas, including the Mason-Dixon line, the U.S.-Canadian border, the shifting boundaries of urban diasporas, and the colonization and confinement of American Indians. They examine the way border studies beckons us to rethink all objects of study and intellectual disciplines as versions of a border problematic.